Indonesian Government Intervention in The Management of Indonesian Migrant Workers’ Remittances: Is It Constitutionally Justified? - Mailinda Eka Yuniza; Annisa Ayuningtyas (Proceedings International Conference on Sustainable Innovation (ICoSI), 2021)
As the newest law on the protection of Indonesian Migrant Workers (IMWs), Law Number 18 of 2017 (Law 18/2017) obliges the Indonesian government to conduct economic protection through remittance management by involving certain institutions. The private nature of migrant workers’ remittances leads to the question of constitutional justification essential for the government's authority to intervene – particularly for Indonesia as a constitutional state in the form of a welfare state – besides the norm applicability skepticism. This paper mainly emphasizes the constitutional silence in regards to state intervention on human resources allocation as it makes the deployment of Indonesian workers abroad constitutionally groundless. As a consequence, this eventually lets the discretion intrude on the remittance, a component of national income that is essentially a private transfer in which the management should be fully controlled by the families.